Project-based learning in higher education: Exploring programming students’ development towards self-directedness - Havenga, HM (South African Journal of Higher Education, 2016)
The purpose of the research reported here was to explore whether the application of project-based learning in higher education could develop programming students’ self-directedness. This research was based on social constructivism and emphasised the construction of knowledge in which students were collaboratively involved. Both quantitative and qualitative methods were employed. The participants in this research were 89 second-year BSc students with a major in Computer Science/Information Technology. Students worked together in a team to develop a programming project. Data collection involved questionnaires, development of a project and a manual as well as various narrative reflections. Findings indicate that participants’ application of project-based learning may contribute to the development of self-directedness.